Analysis of Secondary Metabolites of Shoot, Callus Culture and Field Plant of Chrysanthemum morifolium Ramat - Setiawati, Tia; Ayalla, Alma; Nurzaman, Mohamad; Kusumaningtyas, Valentina A.; Bari, Ichsan (Jurnal ILMU DASAR, 2020)
The chrysanthemum plant (Chrysanthemum morifolium Ramat.) contains many secondary metabolites such as flavonoids and various volatile compounds that can be utilized as drugs. Tissue culture can be an alternative to enhance the production of certain secondary metabolite. The study aimed to determine the types of secondary metabolites that contained in shoot culture, callus and field plants of C. morifolium. The research method was exploration in the laboratory to analyze and compare the content of secondary metabolite from shoot culture, callus and field plants of C. morifolium. Callus was induced by explants of C. morifolium plantlet stems and leaves respectively on MS medium with an addition of 3 ppm 2,4-D + 2 ppm kinetin and 4 ppm 2,4-D. For shoot culture, single nodule explants with one leaf were planted on MS media with the addition of 1 ppm BAP. The secondary metabolite compouds were analized and identified by GC-MS (Gas Chromatography-Mass Spectrometry). The results showed that various types of secondary metabolites contained in shoot culture, callus and field plants of C. morifolium. In callus culture from leaf explants, four compounds from groups of alcohol, acetic acid and organosilicon were identified, whereas in callus culture from stem explants were identified eight compounds from aldehydes, esters, alkanes, and carboxylic acids group. In the shoot culture, nine compounds of alcohol, ketone, aldehyde, cycloalkane and organosilicon group were identified, while in the field plants five compounds were identified from the cycloalkanes, ketones, organoborones and organosilicon group. Some detected compounds have a potential as precursors of alkaloid, phenolic, and flavonoid.Keywords: chrysanthemum, culture, shoots, callus, secondary metabolites.